2015
DOI: 10.3791/53213
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Synthesis of 1,6-Ketoesters Mediated by Ionic Liquids: A Three-component Reaction Enabling Rapid Access to a New Class of Low Molecular Weight Gelators

Abstract: In organic chemistry ionic liquids (ILs) have emerged as safe and recyclable reaction solvents. In the presence of a base ILs can be deprotonated to form catalytically active N-Heterocyclic Carbenes (NHCs). Here we have used ILs as precatalysts in the addition of α,β-unsaturated aldehydes to chalcones to form 1,6-ketoesters, incorporating an anti-diphenyl moiety in a highly stereoselective fashion. The reaction has a broad substrate scope and several functional groups and heteroaromatics can be integrated into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The process of imidazol-2-ylidene formation in imidazolium-based ILs is reported to occur by a simple deprotonation of the carbon atom in-between the two nitrogens of the imidazolium ring. ,, For 1,3-dialkyl-substituted imidazolium ILs Hollóczki et al reported that the equilibrium between the ion pair and the corresponding hydrogen-bonded complex of the free acid and NHC can be shifted toward NHC formation in the presence of the relatively basic anion of the IL …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of imidazol-2-ylidene formation in imidazolium-based ILs is reported to occur by a simple deprotonation of the carbon atom in-between the two nitrogens of the imidazolium ring. ,, For 1,3-dialkyl-substituted imidazolium ILs Hollóczki et al reported that the equilibrium between the ion pair and the corresponding hydrogen-bonded complex of the free acid and NHC can be shifted toward NHC formation in the presence of the relatively basic anion of the IL …”
Section: Introductionmentioning
confidence: 99%
“…32 The process of imidazol-2-ylidene formation in imidazoliumbased ILs is reported to occur by a simple deprotonation of the carbon atom in-between the two nitrogens of the imidazolium ring. 24,25,33 For 1,3-dialkyl-substituted imidazolium ILs Holloćzki et al reported that the equilibrium between the ion pair and the corresponding hydrogen-bonded complex of the free acid and NHC can be shifted toward NHC formation in the presence of the relatively basic anion of the IL. 24 The hypothesis about the presence of trace amounts of highly reactive carbenes in the neat ILs with relatively basic anions might pave the way for a general facile use of in situ formed NHCs in catalytic reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we reported the use of EMIMAc as a precatalyst in the formal Michael addition of α,β-unsaturated aldehydes to chalcones in the synthesis of oxo triphenylhexanoates (OTHOs) [40,41]. In this study it was also shown that one of the OTHOs was a potent low-molecular-weight gelator in hydrocarbon-based solvents.…”
Section: Introductionmentioning
confidence: 97%